EFFECTS OF DIETARY SELENIUM NANOPARTICLES SUPPLEMENTATION ON GROWTH PERFORMANCE, HEMATOLOGY AND BODY COMPOSITION OF OREOCHROMIS NILOTICUS FINGERLINGS - A. Khalid; S. M. Hussain; F. Khalid; M. M. Shahzad; A. Sharif; F. Bashir; M. Asrar (Journal of Animal and Plant Sciences, 2023)
Selenium (Se) is an essential nutrient that plays important role in numerous biological processes and fish feed is the major route of Se supply to fish. A 70-days feeding trial was conducted to evaluate the effects of selenium nanoparticles (Se-NPs) on growth, hematology, and body composition of Oreochromis niloticus fingerlings. A total of 270 fingerlings were assigned into 6 treatment groups. Se-NPs (%) were added to formulate six test diets viz. D-0 (control), D-0.1, D-0.2, D-0.3, D-0.4 and D-0.5, respectively and fed to fingerlings under completely randomized design (CRD). Growth parameters such as weight gain % and FCR started to improve (p≤0.05) when fingerlings were fed on test diet D-0.1 and reached to maximum (229.74%, 1.29) when fish fed on diet D-0.3 as compared to fish fed on control diet (D-0). The values of hematological parameters such as red blood cells (2.90×106mm-3) and white blood cells (7.89×103mm-3) were found to be the maximum (p≤0.05) at D-0.3, while hemoglobin (7.95 and 8.47) was found to be improved significantly at D-0.2 and D-0.3, respectively. Similarly, parameters of body composition i.e. crude protein (20.86%) was improved significantly at D-0.3 while crude fat showed non-significant improvement at D-0.2 and D-0.3 (3.10% and 2.17%) respectively as compared to the control diet. Above D-0.3 level, a significant increase was observed. Fat and moisture contents were found to be maximum at control and D-0.5. So, the results suggested that Se-NPs have the potential to improve the fish body composition and are recommended to be used in fish feed at an optimized level.
Keywords: Selenium; nanoparticles; Nile tilapia; hematology; aquaculture